LAYANAN SISWA DAN PEMBINAAN KARAKTER BANGSA - Paulus Satyo Istandar Tan (LPPM Politeknik Saint Paul Sorong, 2022)
The purpose of liberating education is to develop the potential of learners. Thus, education is essentially freeing man from the bondage of ignorance and backwardness. A person's maturity needs to be developed because humans by nature have been given various potentials. The most important thing is that the student's personality develops, he has understanding and the ability to think independently, has emotional balance, is open to others and has a sense of social responsibility. This research uses qualitative description method method by collecting library data, reading and recording and processing research materials. basic matters that should be given special attention in the implementation of the curriculum in Catholic schools, Value Education in accordance with the spirituality of the founder and the Teaching of the Church, building a